Compositional and electrical properties of line and planar defects in Cu(In, Ga)Se2 thin films for solar cells – a review. Issue 5 (1st March 2016) - Abou‐Ras, Daniel; Schmidt, Sebastian S.; Schäfer, Norbert; Kavalakkatt, Jaison; Rissom, Thorsten; Unold, Thomas; Mainz, Roland; Weber, Alfons; Kirchartz, Thomas; Simsek Sanli, Ekin; van Aken, Peter A.; Ramasse, Quentin M.; et al.
Abstract : The present review gives an overview of the various reports on properties of line and planar defects in Cu(In, Ga)(S, Se)2 thin films for high‐efficiency solar cells. We report results from various analysis techniques applied to characterize these defects at different length scales, which allow for drawing a consistent picture on structural and electronic defect properties. A key finding is atomic reconstruction detected at line and planar defects, which may be one mechanism to reduce excess charge densities and to relax deep‐defect states from midgap to shallow energy levels. On the other hand, nonradiative Shockley–Read–Hall recombination is still enhanced with respect to defect‐free grain interiors, which is correlated with substantial reduction of luminescence intensities. Comparison of the microscopic electrical properties of planar defects in Cu(In, Ga)(S, Se)2 thin films with two‐dimensional device simulations suggest that these defects are one origin of the reduced open‐circuit voltage of the photovoltaic devices. (© 2016 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : This review gives an overview on the current understanding of line and planar defects in Cu(In, Ga)Se2 thin films and their impacts on the corresponding solar‐cell devices.